2020
DOI: 10.2174/0929867325666181031102829
|View full text |Cite
|
Sign up to set email alerts
|

Rho-kinase (ROCK) Inhibitors - A Neuroprotective Therapeutic Paradigm with a Focus on Ocular Utility

Abstract: Background: Glaucoma is a progressive optic neuropathy causing visual impairment and Retinal Ganglionic Cells (RGCs) death gradually posing a need for neuroprotective strategies to minimize the loss of RGCs and visual field. It is recognized as a multifactorial disease, Intraocular Pressure (IOP) being the foremost risk factor. ROCK inhibitors have been probed for various possible indications, such as myocardial ischemia, hypertension, kidney diseases. Their role in neuroprotection and neuronal regeneration ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 153 publications
0
19
0
Order By: Relevance
“…In addition, hyperglycaemia has been shown to increase the expression of monocyte chemoattractant protein-1 (MCP-1/CCL2) and VEGF by vascular endothelial cells and in the vitreous samples from patients with DR [119,120]. It has been reported that the inhibition of RhoA/ROCK1 may attenuate the hypertonicity of endothelial cell caused by high glucose microenvironment, partly block inflammation and prevented considerably the apoptosis of endothelial cells aroused by high glucose [111,112,115,116]. ROCKs involvement in the mechanisms underlying DMO according to the results of preclinical studies.…”
Section: Hyperglycaemiamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, hyperglycaemia has been shown to increase the expression of monocyte chemoattractant protein-1 (MCP-1/CCL2) and VEGF by vascular endothelial cells and in the vitreous samples from patients with DR [119,120]. It has been reported that the inhibition of RhoA/ROCK1 may attenuate the hypertonicity of endothelial cell caused by high glucose microenvironment, partly block inflammation and prevented considerably the apoptosis of endothelial cells aroused by high glucose [111,112,115,116]. ROCKs involvement in the mechanisms underlying DMO according to the results of preclinical studies.…”
Section: Hyperglycaemiamentioning
confidence: 99%
“…ROCK1, is highly expressed in lung, liver, spleen, and kidney [ 106 , 107 , 108 , 109 ]. Both ROCK isomers are also present in ocular tissues and aberrant regulation of ROCK levels plays a role in the pathogenesis of corneal wound healing, glaucoma, diabetic retinopathy, and AMD [ 110 , 111 , 112 ].…”
Section: Rho Kinase and Rock Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ROCK inhibitors have been developed in the past few decades that are predominantly ATP-competitive type 1 inhibitors exemplified by fasudil, the closely related ripasudil/K-115 and the chemically divergent Y-27632 (Yamamoto et al, 2014 and reviewed in Abbhi and Piplani, 2018). However, selectivity is a challenge for these and other molecules.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…Rho kinase (ROCK) inhibitors have great potential in glaucoma, as they not only lower IOP through an increase in conventional aqueous outflow, but they also display neuroprotective effects, thought to have potential benefit in other neurodegenerative conditions such as Alzheimer's disease. 43…”
Section: Kinase Inhibitors H-1337mentioning
confidence: 99%